Breaking Down the Language of Online Racism: A Comparison of the Psychological Dimensions of Communication in Racist, Anti‐Racist, and Non‐Activist Groups. Issue 1 (27th May 2018) - Faulkner, Nicholas; Bliuc, Ana‐Maria
Abstract: The Internet represents a powerful tool for racist groups to build a sense of group consciousness and promote their cause. In the current study, we examined the language used by racist ( n = 87), anti‐racist ( n = 50), and nonactivist ( n = 1379) groups when describing their self‐defining beliefs online. We used computerized linguistic analysis software to measure psychological indicators and antecedents of group consciousness and to examine the persuasive techniques used in online group communication. Racist and anti‐racist groups were similar on some linguistic indicators of group consciousness (e.g., use of words reflecting perceived injustice), but differed on others (e.g., use of words reflecting group identification). Linguistic indicators of antecedents of group consciousness (moral foundations and focus on religion) differed across groups, with racist groups focused more on purity, respect for authority, and religion, and less on fairness than anti‐racist groups. Racist groups also used less cognitively complex language than nonactivist groups (but similar levels to anti‐racist groups). Our results contribute to understanding how racist groups promote their self‐defining beliefs online, and identify several key factors that should be considered when designing policies to reduce racist groups' growth and impact.